A new species and new record of the intertidal rove beetle genus Bryothinusa Casey (Staphylinidae: Aleocharinae: Myllaenini) from Japan - Liu, Tiantian; Ono, Hiroki.; Maruyama, Munetoshi (Zootaxa, 2020)
A new species of the intertidal rove beetle genus Bryothinusa, B. japonica sp. nov. is described, and B. koreana Ahn & Jeon, 2004 is recorded from Japan for the first time. These species are illustrated and compared with similar species. A key to the Japanese Bryothinusa species and a checklist of the known Bryothinusa species are provided.